Relationship of Family Support and Self-Independence of Schizophrenia Outward Patient in RSJ Aceh - Muhammad Rezi Ramdani; Subhan Rio Pamungkas; Reza Maulana (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2016)
Schizophrenia is the worst functional psychosis type which can cause the biggest disorganization disturbance. Patients do not have contacts with the reality, so the the thinking and behaviour become abnormal. Supports from family that was given to the patients can influence the result from the patients’ treatments. The purpose from this research is to know the correlation between family’s supports and the independent of schizophrenia patients. This research was a descriptive analitic with cross sectional approachment. The samples were taken using quota sampling method. Total sample from this research was 43 respondents. Datas were gathered by using questionnairs with interview technique. The result from this research showed that there was a correlation between family’s supports and the independent of schizophrenia patients, where the value of the coefficient correlation (r) was 0,406 with p value = 0,007 (p0,05). So family’s supports must be increased to support independence of patient until we get the optimal result.